HAZOP Analysis of Air Tank on Dust Collector: Integrating Risk Assessment and Skill Development in Mining - Yafi Nur Hanif; Agus Pramono; Suhendar Suhendar (International Journal of Multidisciplinary Research of Higher Education, 2026)
Air tank dust collectors are essential for safeguarding air quality and operational safety in industrial environments. Nevertheless, these systems are highly susceptible to hazards arising from abnormal pressure and temperature conditions. This study employs Hazard and Operability Analysis (HAZOP) to systematically identify and evaluate risks associated with air tanks in dust collection equipment. Conducted within an industrial setting, the analysis highlights that excessive pressure and elevated temperatures can result in severe outcomes, including fires, explosions, and mechanical failure. To mitigate these risks, the study recommends the installation of safety valves, integration of advanced pressure and temperature sensors, and implementation of rigorous maintenance schedules. The findings confirm that HAZOP provides a structured framework for detecting potential hazards and developing preventive measures, thereby enhancing reliability and safety in industrial operations. This research contributes to the broader field of industrial risk management by demonstrating the effectiveness of HAZOP in addressing critical safety challenges related to pressure and temperature control.